Pengaruh Love of Money, Machiavellianisme dan Penalaran Moral terhadap Persepsi Etis Mahasiswa Akuntansi dengan Sensitivitas Etis sebagai variabel Moderasi - Muhdar, Nurfadillah; Sinen, Kasim; Kusumaningrum, Sheila (Owner : Riset dan Jurnal Akuntansi, 2026)
This study aims to examine and analyze the effect of love of money, Machiavellianism, and moral reasoning on accounting students’ ethical perceptions, with ethical sensitivity as a moderating variable. The research involved 90 respondents. Data were collected through questionnaires distributed to accounting students of the 2021 cohort at Khairun University using a five-point Likert scale via Google Forms. The data were analyzed using a quantitative approach with Partial Least Squares–Structural Equation Modeling (PLS-SEM) through SmartPLS 4 software. The results indicate that love of money and Machiavellianism have no significant effect on accounting students’ ethical perceptions. In contrast, moral reasoning has a positive and significant effect on ethical perceptions. Furthermore, the findings reveal that ethical sensitivity does not moderate the relationship between love of money, Machiavellianism, and moral reasoning on accounting students’ ethical perceptions.